2022
DOI: 10.3390/antiox11081443
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Analyses and Evaluation of Antioxidant Activity in Purple Kohlrabi Sprouts after Exposed to UVB Radiation

Abstract: Various metabolites act as plant defense molecules due to their antioxidant abilities. This study aimed to investigate the influence of UVB irradiation on the accumulation of metabolites, including primary metabolites (sugar, sugar alcohols, amino acids, organic acids, and an amine) and secondary metabolites (anthocyanins, fatty acids, and phenolic acids), and its synergistic antioxidant ability, in purple kohlrabi sprouts. Metabolite analyses revealed a total of 92 metabolites in the sprouts. Specifically, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Only purple kohlrabi contains anthocyanins and has a higher phenylpropanoid content than green kohlrabi [ 6 ]. Various studies have shown cruciferous vegetables, including kohlrabi, are beneficial for human health, as they contain abundant ascorbic acid, carotenoids, and tocopherol [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only purple kohlrabi contains anthocyanins and has a higher phenylpropanoid content than green kohlrabi [ 6 ]. Various studies have shown cruciferous vegetables, including kohlrabi, are beneficial for human health, as they contain abundant ascorbic acid, carotenoids, and tocopherol [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of Hydrophilic Compounds by GC-TOFMS. The hydrophilic metabolites were extracted using the methodology outlined in a recent work by Yeo et al 45 with minor modifications. Briefly, 1 mL of water, CHCl 3 , and MeOH in a ratio of 1:1:2.5 (v/v/v) was added to 10 mg of N. tazetta tissues (callus, adventitious root, and stem) generated in vitro, followed by the addition of 60 μL of 0.2 g/L adonitol as an internal standard.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The cultivation conditions and the type and parameters of the production processes used affect the chemical composition and properties of raw materials as well as semi-finished and finished products. Research into the effect of UVB radiation on changes in the composition of primary and secondary metabolites in plants was conducted by Yeo et al [ 5 ]. Purple kohlrabi sprouts ( Brassica oleracea var.…”
Section: Bioactive Compounds In Technological Processes Of Food Produ...mentioning
confidence: 99%
“…The study indicated that UVB irradiation could induce an overall alteration in metabolite composition. Increased levels of secondary metabolites, such as anthocyanins and phenolic acids and ABTS free radical scavenging ability were observed during UVB irradiation [ 5 ].…”
Section: Bioactive Compounds In Technological Processes Of Food Produ...mentioning
confidence: 99%